PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI SMA NEGERI 1 AKABILURU - Angrainy, Siti Elfina (Jurnal Edukasi dan Penelitian Matematika, 2025)
An important function of learning outcomes is as a measure of the success of the learning process. Success in learning is directly proportional to the level of achievement. Data on learning outcomes from class XI at SMA Negeri 1 Akabiluru, showed that the results were still below average. Therefore, it is planned to use the Discovery Learning model. The purpose of the study was to determine how well the learning outcomes of grade XI students at SMA Negeri 1 Akabiluru after using conventional learning in class or using the DL model. This quasi-experimental study used a posttest-only design with a non-equivalent control group. Since the P-value of the t-test =0.000, H0 can be rejected. Based on these results, the DL model outperformed the conventional learning method.Keywords– Discovery Learninng Model, Learning Outcomes, conventional learning